Frequently Asked Questions about Stormwater Wet Ponds - Ange Asanzi; Miranda Carver Martin; Michelle Atkinson; Chamoda P. D. Dissanayake Mudiyanselage; Basil V. Iannone III; Eban Bean; Alexander J. Reisinger; Mary Lusk; Dail Laughinghouse; Paul Monaghan (EDIS)
This publication addresses some of the most frequent questions that residents ask regarding the function and maintenance of their stormwater ponds. Written by Ange Asanzi, Miranda Carver Martin, Michelle Atkinson, Chamoda P. D. Dissanayake Mudiyanselage, Basil V. Iannone III, Eban Bean, Alexander J. Reisinger, Mary Lusk, Dail Laughinghouse, and Paul Monaghan, and published by the UF/IFAS Department of Agricultural Education and Communication, August 2024.